2023
DOI: 10.1007/s11883-023-01184-1
|View full text |Cite
|
Sign up to set email alerts
|

Obicetrapib: Reversing the Tide of CETP Inhibitor Disappointments

John J. P. Kastelein,
Andrew Hsieh,
Mary R. Dicklin
et al.

Abstract: Purpose of Review To discuss the history of cardiovascular outcomes trials of cholesteryl ester transfer protein (CETP) inhibitors and to describe obicetrapib, a next-generation, oral, once-daily, low-dose CETP inhibitor in late-stage development for dyslipidemia and atherosclerotic cardiovascular disease (ASCVD). Recent Findings Phase 1 and 2 trials have evaluated the safety and lipid/lipoprotein effects of obicetrapib as monotherapy, in conjunction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“… 50 Analyses of lipoprotein particle subpopulations by nuclear magnetic resonance indicated that higher CETP concentrations are associated with lower levels of L-HDL, consistent with our study, and with more small VLDL particles. 51 It is possible that highly specific next-generation CETP inhibitors, such as obicetrapib 52 will be more effective. In addition, CETP inhibitors appear to reduce incident type 2 diabetes through an unclear mechanism.…”
Section: Discussionmentioning
confidence: 99%
“… 50 Analyses of lipoprotein particle subpopulations by nuclear magnetic resonance indicated that higher CETP concentrations are associated with lower levels of L-HDL, consistent with our study, and with more small VLDL particles. 51 It is possible that highly specific next-generation CETP inhibitors, such as obicetrapib 52 will be more effective. In addition, CETP inhibitors appear to reduce incident type 2 diabetes through an unclear mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been shown in ACCELERATE and REVEAL trials [ 119 ]. A new CETP inhibitor, obicetrapib, which has demonstrated excellent safety and tolerability in phase 1 and 2 trials (ROSE2 or Systematic Coronary Risk Evaluation ROSE2 study) [ 120 ], is being studied in a phase 3 trial and is anticipated to be a promising agent in the prevention of CVDs.…”
Section: Hdl Interaction With Major Proteins and Receptors Involved I...mentioning
confidence: 99%
“…To date, five CETP inhibitors including torcetrapib, dalcetrapib, evacetrapib, anacetrapib, and, most recently, obicetrapib have reached late-stage clinical development for ASCVD risk reduction (reviewed in [24]). It has been observed that all CETP inhibitors have a significantly positive effect on apolipoprotein A-I and HDL-C concentrations.…”
Section: Introductionmentioning
confidence: 99%